Scheme of arrangement (SOA) in abandoned housing projects: A case study of Malaysia - Md Dahlan, Nuarrual Hilal (2012)
Abandoned housing projects is a formidable problem in Malaysia's housing industry. Although the Malaysian government has enacted law and formulated policies to govern the housing industry since it achieved Independence in 1957, abandoned housing projects remains a recurrent problem until today.The real victims are the purchasers themselves.When an insolvent housing developer company is subject to Scheme of Arrangement (SOA), the affair and business of the company are taken over by the appointed SOA Manager. The SOA Manager may rehabilitate the abandoned projects left by the insolvent housing developer companies, if the projects are viable for rehabilitation with the majority approval of the creditors and where there are adequate funds to finance the rehabilitation.Otherwise, if the project is not viable, particularly because there are insufficient funds to run the rehabilitation or the problems of the abandoned housing projects are too complicated, the projects may be stalled forever without any prospects for rehabilitation, to the detriment of the purchasers.This article discusses the law and practice in the rehabilitation of abandoned housing projects in Malaysia of housing developer companies under SOA.At the end of this paper, the author proposes certain suggestions in facing the problems of abandoned housing projects of the housing developer companies under SOA and its rehabilitation in Malaysia.